‘THE INVIABLE AND VIABLE UNIQUE CHARACTER OF SILVERPOINT DRAWING FROM THE PAST TO CURRENT PRACTICE’ - Ernesto Carlos Pujazon Patron; Jose Domingo Elias; Fuad Arif; Mumtaz Mokhtar, (INTERNATIONAL JOURNAL OF HERITAGE, ART AND MULTIMEDIA (IJHAM), 2024)
The use of Metalpoints such as silver, bronze (Brass), copper, gold or lead are of the most gentle and delicate techniques applied by the Renaissance masters in Europe predating the introduction of graphite. There is a wealth of detailed information available online. Metalpoint was a popular drawing and writing technique from the 14th to the early 16th century. This technique involves dragging a metal-stylus across a substrate coated with a somewhat abrasive emulsion leaving small particles of metal dust over the surface to create a mark. These metal-rods oxidate over a different period of time which is altered by the environmental circumstances, changing the drawing appearance. Similar to a pencil rendering, the silver line oxidises and becomes black. Although it is difficult to utilise metalpoint to produce a specific tiny mark, it is a desired tool for a highly talented draughtsman. This paper discusses the practical approach to substrate preparation; the hatching and cross-hatching technique employed by the masters and contemporary artists in addition to the provocative drawing and sensual rendering impact of the finished drawing.